Using the reflectance parameters as covariates of the organic matter content in fallow soils - K.G. Giniyatullin; I.A. Sahabiev; E.V. Smirnova; A.A. Valeeva; S.S. Ryazanov; L.I. Latypova (Учёные записки Казанского университета: Серия Естественные науки)
This article estimates whether the reflectance parameters of air-dried (< 0.25 mm) soil samples in the visible and infrared (IR) spectral regions can be used as a covariate of the soil organic matter content (SOM) in old-arable horizons of fallows. A significant correlation of the SOM content was revealed only with the intensity of the absorption band 1630 cm–1 and the area of the absorption band 1706–1537 cm–1. Low correlations in the IR range were associated with the chemical heterogeneity of the SOM inherited from the arable soil and the newly formed SOM under the fallows. Closer correlations were observed between the SOM and reflectance in the red (R) band of the visible spectrum, the obtained correlation coefficient (r) was –0.76 for the 0–5 cm layer and –0.73 for the 5–10 cm layer. It was shown that the use of reflectance in the R-band for cokriging results in a more accurate spatial prediction of the SOM distribution with a minimal sample compared to ordinary kriging. Improved maps of the SOM content can provide a more realistic prediction of the sequestration of CO2 in fallow soils, as well as its emission from fallows during land-use change.